MARKETING KNOWLEDGE USEFULNESS - IN A QUEST FOR THE USER PERSPECTIVE APPROACH - - Uzelac, Nikola (Economic Annals, 2006)
Marketing knowledge usefulness has been the object of increasing concern within the discipline. Numerous shortcomings of its various aspects have been identified, elaborated and accompanied with sophisticated solutions. Further progress in this direction is potentially much greater in a case of acceptance of the user perspective approach. In relation to the behaviour of a marketing manager, simple acceptability-affordability-availability-awareness concept is presented. It redirects our attention to the manager’s point of view and serves as an illustration of highly desirable more complex works. Proposed development leads to the creation and integration of behaviour models specific to each group of marketing knowledge stakeholders: managers, students, academics and society.